Psychographic And Behavioral Segmentation Of Food Delivery Application Customers To Increase Intention To Use - Zárate, Jorge Luis Bocanegra (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence